Diblock copolymers of polystyrene‐b‐poly(1, 3‐cyclohexadiene) exhibiting unique three‐phase microdomain morphologies. Issue 16 (29th March 2016) - Misichronis, Konstantinos; Chen, Jihua; Kahk, Jong K.; Imel, Adam; Dadmun, Mark; Hong, Kunlun; Hadjichristidis, Nikos; Mays, Jimmy W.; Avgeropoulos, Apostolos
ABSTRACT: The synthesis and molecular characterization of a series of conformationally asymmetric polystyrene‐ block ‐poly(1, 3‐cyclohexadiene) (PS‐ b ‐PCHD) diblock copolymers (PCHD: ∼90% 1, 4 and ∼10% 1, 2), by sequential anionic copolymerization high vacuum techniques, is reported. A wide range of volume fractions (0.27 ≤  ϕ PS  ≤ 0.91) was studied by transmission electron microscopy and small‐angle X‐ray scattering in order to explore in detail the microphase separation behavior of these flexible/semiflexible diblock copolymers. Unusual morphologies, consisting of PCHD core(PCHD‐1, 4)–shell(PCHD‐1, 2) cylinders in PS matrix and three‐phase (PS, PCHD‐1, 4, PCHD‐1, 2) four‐layer lamellae, were observed suggesting that the chain stiffness of the PCHD block and the strong dependence of the interaction parameter χ on the PCHD microstructures are important factors for the formation of this unusual microphase separation behavior in PS‐ b ‐PCHD diblock copolymers. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1564–1572 Abstract : This work addresses the synthesis and characterization of diblock copolymers consisting of polystyrene (PS) and poly(cyclohexadiene) (PCHD). As the PCHD content increases, unexpected morphologies are observed such as core–shell cylinders and three‐phase four‐layer lamellae, which are mainly formed due to the alternations in the PCHD polymer chains introduced by the −1, 2 and −1, 4 microstructures and enhanced by the high conformational asymmetry of the system.